Investigation on Power Battery To Be Used for Electric Go-Kart Development - MOHAMMAD AIDID BIN RAHMAN (Progress in Engineering Application and Technology, 2021)
The title of this project is to investigate or identify the battery power that will be used for the construction of electric go-karts. Besides that, the charging time on the batteries also was included in this project. Based on the research, all the information was be summarized to find out a suitable battery for electric go-kart development. The trending or demand for lithium battery was increased year by year compared to the lead-acid. It all because the performance of the lithium battery on density, weight, and capacity give it the most demand on the market. The selection of the battery was used the matrix method to compare which battery has a high point of recommendation compare to lead-acid batteries. So, from the selection, the batteries need to be tested by load test to find out the internal resistance. The value of the internal resistance needs to find out because it will give the impact of safety on the battery, which is the higher internal resistance with the higher current will heat up the battery that may cause of exploding. So the lithium battery has a lower internal resistance with a higher current, which means it was safe to be used. On the charging time, the calculation will be to find out the power of the batteries and the capacity of the battery charger to get the time taken to charge the batteries. The different output current on the DC charger will give different charging times is taken, which is the higher output current give the lower time of charging. From this project, it will come out with the data to support the lithium battery as a suitable and safe to be used in the development of electric go-kart. Besides that, the DC charger with a higher output current will cut off the time taken to charge the battery.